Feasibility assessment of electrochemical chlorination for direct potable reuse - Kaichao Yang; Ibrahim M. Abu-Reesh; Zhen He (Journal of Hazardous Materials Letters)
Electrochemical chlorination is promising for direct potable reuse (DPR) with zero-chemical-input and was investigated in this study for its application potential in reverse osmosis (RO)-based and non-RO-based DPR processes. Treatment of the simulated reclaimed water from non-RO-based trains showed satisfactory chlorine evolution compared to that from the RO-based trains. Under an applied current of 100 mA, a desired free chlorine concentration of 2 mg Cl2 L−1 was obtained within a short reaction time of 3.5 s. Consistent chlorine evolution performance was achieved in continuous experiments for 500 cycles, and the effluent pH was within the range of potable water guidelines (6.5 – 8.5). Electrochemical chlorination showed competitive disinfection performance compared to conventional chemical chlorination (7 log inactivation of E. coli within 60 s) at a low energy demand of ∼ 0.05 kWh m−3. The results of this preliminary investigation encourage the further exploration of electrochemical chlorination for DPR through the use of noble-metal-free anodes, utilization of renewable energy sources, removing persistent organic contaminants, and examining the synergy with RO-based DPR.